What is a bird? : an exploration of anatomy, physiology, behavior, and ecology - Williams, Tony D.; Williams, Tony D.; Clements, Andy; Clements, Andy; Clarke, Julia A.; Eliason, Chad M.; MacDougall-Shackleton, Scott A.; McWilliams, Scott (Scott Robert); MacDougall-Shackleton, Elizabeth Anne, 1969-; Bonier, Frances (Princeton University Press, 2020)
There are some 10,000 bird species in existence today, occupying every continent and virtually every habitat on Earth. The variety of bird species is truly astounding, from the tiny bee hummingbird to the large flightless ostrich, making birds one of the most diverse and successful animal groups on the planet. Taking you inside the extraordinary world of birds, What Is a Bird? explores all aspects of these remarkable creatures, providing an up-close look at their morphology, unique internal anatomy and physiology, fascinating and varied behavior, and ecology. It features hundreds of color illustrations and draws on a broad range of examples, from the familiar backyard sparrow to the most exotic birds of paradise. A must-have book for birders and armchair naturalists, What Is a Bird? is a celebration of the rich complexity of bird life.